The sex-specific influence of FTO genotype on exercise intervention for weight loss in adult with obesity. Issue 12 (2nd December 2022) - Wang, Weimin; Yang, Ke; Wang, Shujie; Zhang, Jiani; Shi, Yanyun; Zhang, Huawei; Jin, Danping; Gu, Ruoxi; Zeng, Qiang; Hua, Qian
ABSTRACT: The impact of exercise on weight loss varies significantly among individuals, and genes play a critical role. This study aims to explore whether the FTO gene variant (rs8050136) affects the influence of exercise on weight. The study initially recruited 240 Han Chinese adults with obesity, and 178 of them (101 men, 77 women, aged from 21 to 60) completed a 12-week moderate aerobic exercise programme. The participants were genotyped and obesity-related data were collected before and after the intervention. The intensity and the amount of exercise were precisely monitored. After the intervention, most obesity-related parameters of the participants showed a significant decrease. For muscle and lean body mass, significant change was only observed in males ( P < 0.001) but not females ( P = 0.205, P = 0.200 respectively). Importantly, for weight and BMI loss, we observed a genotype-by-gender interaction ( P = 0.041, P = 0.042 respectively, adjusted for age, exercise time and baseline value). In the further analysis, after stratified for gender, the exercise-induced weight loss ( P = 0.008), BMI loss ( P = 0.010), muscle mass loss ( P = 0.005) and lean body mass loss ( P = 0.004) showed greater decrease in male subjects carrying at least one A allele compared to non-carriers. In conclusion, our study suggests that in Han Chinese population with obesity, carrying "obese risk gene" FTO (rs8050136) does not lead to the resistance to weight management intervention. More importantly, in male subjects, carrying FTO risk allele would even lose more weight than non-carriers after exercise intervention. Highlights For Han Chinese adults with obesity, carrying "obese risk gene" FTO could still achieve weight loss through exercise. Males carrying FTO risk allele would lose more weight than non-carriers after a 12-weeks exercise programme.